2-Dimensional networks assembled using 4′-functionalized 4, 2′:6′, 4″-terpyridines and Co(NCS)2. (8th January 2016) - Klein, Y. Maximilian; Prescimone, Alessandro; Constable, Edwin C.; Housecroft, Catherine E.
Graphical abstract: A series of 2-dimensional (4, 4) nets formed when Co(NCS)2 reacts with divergent 4, 2′:6′, 4″-terpyridine ligands functionalized in the 4′-position with OMe, OEt, O n Pr or t Bu groups is reported; variation in packing of the nets as a function of the 4′-substituent is discussed. Abstract: A series of 2-dimensional (4, 4) nets formed in reactions of Co(NCS)2 with divergent 4′-functionalized-4, 2′:6′, 4″-terpyridine ligands is reported, and the effects of the 4′-substituent R (ligand1, R = t Bu;5, R = MeO;6, R = EtO;7, R = n PrO) on the packing of the nets are described. The 2D-coordination networks in [Co(NCS)2 (6 )2 ·4CHCl3 ] n and [Co(NCS)2 (7 )2 ·4CHCl3 ] n are essentially isostructural. On going to [Co2 (NCS)4 (5 )4 ·2CHCl3 ·1.5MeOH] n, modification of both the geometry of the rhombuses that comprise the network, and the packing occurs. All three structures feature head-to-tail π-stacking of 4′-(4-alkoxyphenyl) units, but with variation in their relative orientations. In contrast, [Co(NCS)2 (1 )2 ·0.5H2 O] n comprises double layers of (4, 4) nets with hydrophobic coatings of tert -butyl groups, leading to alternating wide and close spacings between adjacent nets.